Parent’s factors influence on immunization status of their preschool-aged children at Hospital Universiti Sains Malaysia (Hospital USM) - Ariffin, Norhafiza (Universiti Sains Malaysia, 2013)
Immunization is important for the children in order to prevent them from getting dangerous diseases. Parents are important people who are responsible in determining the completeness of immunization having by the children. This research was done to determine association between parent’s factors and children immunization status. Parent’s factors included are parent’s soeio-demographic data, knowledge, attitude and information obtained regarding immunization. This research was a cross-sectional study research and used self-administrated questionnaire as research instrument. Respondents included were parents who care for their hospitalized child in pediatric ward Hospital USM. Total of 65 parents were involved in this study. The data obtained then were analyzed using Statistical Package for Social Sciences (SPSS) version 20.0. The data analyses used were descriptive statistic and Fisher’s Exact test. Result showed that 83.1% of the respondent had good knowledge about immunization. Besides, 58.5% respondent showed positive attitude toward immunization having by their children. Result also showed that there was no significant association between parent’s socio-demographic data and preschool-aged children immunization status. Finding also showed that there was no significant association between parent’s attitude and information obtained about immunization and their preschool-aged children immunization status. The p-values were 0.565 and 1.000 respectively. However, the significant association was found between parent’s knowledge about immunization and children immunization status with p-value was 0.004. This research found that parent socio-demographic data, their attitude and information obtained regarding immunization is not the factors that contribute to completeness and non-completeness of immunization. However, parental knowledge level about immunization was the factor that will contribute to the status of children immunization.